Critical analysis of the latin american discourse or “making politics talk” - Pineda, Alicia (Quórum Académico, 2022)
The need for a Latin American critical discourse analysis (CDA) theory and method capable of “making politics speak, endogenously” is analyzed. The methodology: hermeneutic, abductive reflection. Conclusions: 1) Latin American CDA does require systematized theories and methods in a revisited critical semiotics that undresses hegemony. 2) The Latin American ACL must contemplate the resemantization of politics as an ingredient linked, historically, in this context to domination, and not only, marginally, to ideas, to the intellect. 3) The social development strategy of the AC is considered as of public interest, and consequently, should be the subject of public policies.